The Effects of Nuclear Factor Erythroid 2 (NFE2)-Related Factor 2 (Nrf2) Activation in Preclinical Models of Peripheral Neuropathic Pain - Paramita Basu; Dayna L. Averitt; Camelia Maier; Arpita Basu (MDPI AG, 2022)
Oxidative stress, resulting from an imbalance between the formation of damaging free radicals and availability of protective antioxidants, can contribute to peripheral neuropathic pain conditions. Reactive oxygen and nitrogen species, as well as products of the mitochondrial metabolism such as superoxide anions, hydrogen peroxide, and hydroxyl radicals, are common free radicals. Nuclear factor erythroid 2 (NFE2)-related factor 2 (Nrf2) is a transcription factor encoded by the NFE2L2 gene and is a member of the cap 'n' collar subfamily of basic region leucine zipper transcription factors. Under normal physiological conditions, Nrf2 remains bound to Kelch-like ECH-associated protein 1 in the cytoplasm that ultimately leads to proteasomal degradation. During peripheral neuropathy, Nrf2 can translocate to the nucleus, where it heterodimerizes with muscle aponeurosis fibromatosis proteins and binds to antioxidant response elements (AREs). It is becoming increasingly clear that the Nrf2 interaction with ARE leads to the transcription of several antioxidative enzymes that can ameliorate neuropathy and neuropathic pain in rodent models. Current evidence indicates that the antinociceptive effects of Nrf2 occur via reducing oxidative stress, neuroinflammation, and mitochondrial dysfunction. Here, we will summarize the preclinical evidence supporting the role of Nrf2 signaling pathways and Nrf2 inducers in alleviating peripheral neuropathic pain.